DEKSTROSA MONOHIDRAT KUALITAS FARMASI DARI PATI Manihot ecsulenta, Metroxylon sagu, Zea mays, Oryza sativa, dan Triticum - Kartika, Bayu Mahdi; Khojayanti, Lely; Nuha, .; Listiana, Shelvi; Kusumaningrum, Susi; Wijaya, Ayustiyan Futu (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2019)
Pharmaceutical Grade Dextrose Monohydrate from Manihot ecsulenta, Metroxylon sagu, Zea mays, Oryza sativa, dan Triticum Starch ABSTRACT Pharmaceutical-grade dextrose monohydrate, one of raw materials used as active pharmaceutical ingredients (API) and additives, can be made from starch. There are five types of local Indonesian commercial starch that are potentially used, namely tapioca (Manihot esculenta), sago (Metroxylon sagu), corn (Zea mays), rice (Oryza sativa), and wheat (Triticum) starch. This study aimed to compare these five starches as raw materials for preparing pharmaceutical-grade dextrose monohydrate which was expected to meet the requirements of the Indonesian Pharmacopoeia (5th Edition) and the United States Pharmacopeia (USP). The starch was converted into dextrose monohydrate through liquefaction hydrolysis, saccharification hydrolysis, activated carbon purification and filtration, ion exchange purification, evaporation, crystallization and drying. High Performance Liquid Chromatogram (HPLC) and the Luff-Schoorl methods were used for dextrose equivalent value (DE) analysis. The results showed that only three of the starch types produced pharmaceutical-grade dextrose monohydrate, namely (DE) sago starch (107.23% and 100.77%), corn starch (97.86% and 96.19%), and tapioca starch (85.18% and 99.20%).Keywords: dextrose equivalent, dextrose monohydrate, hydrolysis, pharmaceutical grade, starchABSTRAKDekstrosa monohidrat kualitas farmasi, salah satu bahan baku yang digunakan sebagai active pharmaceutical ingredient (API) dan bahan tambahan, dapat dibuat dari bahan pati-patian. Terdapat lima jenis pati komersial lokal Indonesia yang berpotensi digunakan yakni pati tapioka (Manihot esculenta), pati sagu (Metroxylon sagu), pati jagung (Zea mays), pati beras (Oryza sativa), dan pati gandum (Triticum). Penelitian ini bertujuan membandingkan lima jenis pati tersebut sebagai bahan baku pembuatan dekstrosa monohidrat kualitas farmasi yang diharapkan mampu memenuhi standar persyaratan dari Farmakope Indonesia Edisi V dan United States Pharmacopeia (USP). Pati diubah menjadi dekstrosa monohidrat melalui hidrolisis likuifikasi, hidrolisis sakarifikasi, pemurnian karbon aktif dan filtrasi, pemurnian ion exchange, evaporasi, kristalisasi dan pengeringan. Metode High Performance Liquid Chromatogram (HPLC) dan Luff-Schoorl digunakan untuk analisis dextrose equivalent (DE). Hasil penelitian menunjukkan hanya tiga jenis pati yang menghasilkan dekstrosa monohidrat kualitas farmasi, yakni (DE) pati sagu (107,23% dan 100,77%), pati jagung (97,86% dan 96,19%), dan pati tapioka (85,18% dan 99,20%).Kata kunci: dekstrosa monohidrat, dextrose ekuivalen, hidrolisis, kualitas farmasi, pati